The The Utilization of Wordwall as a Multisensory English Vocabulary Learning Tool for Slow Learners: A Case Study of Teacher Experience - Rahayu Wulandari; Rahmah Fithriani (Talenta Publisher, 2026)
This study examines the utilization of Wordwall as a multisensory instructional tool for teaching English vocabulary to slow learners in inclusive EFL classrooms at the junior high school level. Slow learners often encounter difficulties in vocabulary acquisition due to slower cognitive processing, limited working memory, and challenges in retention. Consequently, instructional approaches must incorporate repetition, explicit explanation, and adaptive strategies aligned with learners’ cognitive characteristics.This research employed a qualitative case study design involving two participants: an English teacher and a shadow teacher experienced in teaching slow learners using Wordwall. Data were collected through semi-structured interviews and teacher reflective documents, and analyzed using thematic analysis to identify patterns related to multisensory instruction, pedagogical adaptation, and technology integration.The findings indicate that Wordwall functions as a complementary instructional tool that enhances learners’ motivation, engagement, and participation. Its visual, auditory, and interactive features facilitate vocabulary learning through image-word association, pronunciation support, and repeated exposure. However, vocabulary mastery remains dependent on explicit instruction, scaffolding, and continuous teacher mediation. Teachers assume critical roles as instructional designers, facilitators, motivators, and evaluators, adapting content, pacing, and task complexity to meet learners’ needs.Despite its pedagogical potential, several challenges were identified, including technological constraints, students’ limited digital literacy, the need for differentiated instruction, and concerns regarding assessment validity. Overall, the study concludes that the effectiveness of Wordwall is determined not by its technological features alone but by its integration within adaptive and pedagogically informed instructional practices.